2016
DOI: 10.1017/s1930297500003089
|View full text |Cite
|
Sign up to set email alerts
|

Number preferences in lotteries

Abstract: We explore people’s preferences for numbers in large proprietary data sets from two different lottery games. We find that choice is far from uniform, and exhibits some familiar and some new tendencies and biases. Players favor personally meaningful and situationally available numbers, and are attracted towards numbers in the center of the choice form. Frequent players avoid winning numbers from recent draws, whereas infrequent players chase these. Combinations of numbers are formed with an eye for aesthetics, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 100 publications
4
26
0
Order By: Relevance
“…From the two datasets, players seem to have a high preference for small numbers (single digits) especially 1 and 9. Various authors including Stern & Cover, (1989), Oyeleke & Otekunrin, (2014) and Wang et al (2016) reported a preference for small numbers. Also, players have a preference for numbers with repeated digits in the two datasets (11, 22, ... 88, which are above the mean for all but one case).…”
Section: Bazooka Gamementioning
confidence: 99%
See 4 more Smart Citations
“…From the two datasets, players seem to have a high preference for small numbers (single digits) especially 1 and 9. Various authors including Stern & Cover, (1989), Oyeleke & Otekunrin, (2014) and Wang et al (2016) reported a preference for small numbers. Also, players have a preference for numbers with repeated digits in the two datasets (11, 22, ... 88, which are above the mean for all but one case).…”
Section: Bazooka Gamementioning
confidence: 99%
“…It is related to the gambler's fallacy (GF) where people tend to believe that an event is less likely to occur because of its recent occurrence. Lottery players with this belief usually avoid recently drawn number combinations (Clotfelter & Cook, 1993;Suetens et al, 2016;Wang et al, 2016). A contrasting fallacy is the hot-hand fallacy (HHF) where people believe that an event is more likely to occur because of recent streaks of occurrence of that event (Suetens et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations